Assessement of ICT Literacy Level among Senior Schools Biology Teachers in Kwara State, Nigeria - LUWOYE, AKINDEYI; Afolabi, Ojo Kayode; Adesanya, Emmanuel A (Bioeduca : Journal of Biology Education, 2025)
Information and communication technology (ICT) has become an important tool in all aspects of life ranging from medicine to security and education. It is an indispensable part of education system and has brought about quality education. This study, therefore, assessed ICT literacy level of senior school biology teachers' in Kwara State, Nigeria. The study investigated the influence of age, teaching experience and gender on ICT literacy level among senior school biology teachers in Kwara State. The study was a survey research type. The sample comprised of two hundred and fifty-nine (259) biology teachers from one hundred and nineteen (119) public & private senior secondary schools in Kwara State. Purposive sampling technique was adopted. The instrument entitled" Biology Teachers' ICT Literacy Level Questionnaire" (BTICTLLQ) was validated by three experts in science education and educational technology and its reliability index was 0.72 using Cronbach's Alpha. Data were analyzed using frequency, percentages, cross tabulation tables and Chi-square at 0.05 level of significance. The findings of the study revealed that: ICT literacy level among teachers is gender sensitive; the age of teachers' influence their ICT literacy level; and there was significant difference in ICT literacy level of teachers on the bases experience. The study concluded that when biology teachers are ICT literate, the use of ICT resources could enhance teaching and learning of biology. The study recommended that intervention inform of seminars and workshops should be organized on regular basis to improve ICT literacy level and utilization of ICT tools by senior school biology teachers.